Narrative Voice and Perspective in Raja Rao’s ‘The Serpent and the Rope’: An Analysis of First-Person Narrative - Sinha, Dr. Arpana (Journal of Advanced Research in English & Education, 2019)
Raja Rao’s ‘The Serpent and the Rope’ is a seminal work in Indian English literature, distinguished by its philosophical density and its unconventional narrative structure. This article argues that the novel’s formal and philosophical power is fundamentally rooted in its use of a first-person narrative, with the protagonist Ramaswamy acting as the sole narrator. This choice of perspective is not a mere stylistic decision but a deliberate formal device that allows the novel to become a direct and unfiltered record of a consciousness in turmoil. The first-person voice serves as the unifying thread for the novel’s disparate elements, from its philosophical digressions to its mythological allusions, giving the entire work a sense of coherence and purpose. This article analyses how this perspective blurs the line between autobiography and fiction, allows for a deeply introspective and confessional tone, and formalises the protagonist’s journey as a cross-cultural and epistemic quest. This article posits that the novel’s narrative perspective is the key to understanding its profound exploration of the nature of the self, as the narrator’s voice evolves from a limited, personal ‘I’ to a universal, non-dual consciousness, making the very act of narration a central component of the philosophical inquiry.